Gościnne myślenie świata. Podmiotowość zwierząt w perspektywie kosmopolitycznej - Mitek-Dziemba, Alina (Civitas. Studia z filozofii polityki, 2016)
The article aims to discuss the question of the political agency and the subjecthood of animals within the framework of cosmopolitan thinking that features the notions of citizenship of the world and cosmopolitan right (as a condition of ‘perpetual peace’ in Immanuel Kant’s philosophy). Cosmopolitanism, as elucidated by Kwame Anthony Appiah, is in its basic meaning a gesture of transcending the particularity of political interests and alliances to approach the whole universe. It involves going beyond the bonds of kinship and citizenship and embracing a global biological community on the basis of moral obligations arising from coexistence and cohabitation with other beings, regardless of how distant and alien they are. This broad, indeed hospitable, definition of cosmopolitanism seems to invite interspecies applications, especially in relation to the far-reaching consequences the needs of one species to dominate the Earth that give rise to a sense of community with a distinct set of moral commitments.